PERILAKU KONSUMEN COFFEE SHOP KOTA SERANG DALAM MEMBANGUN USULAN PENELITIAN PEMASARAN - Hanafiah, Hafidz; Hidayat, Ardi; Aziz, Abdul (Bhinneka Multidisiplin Journal, 2025)
Consumer behavior is a branch of marketing management that studies the behavior or attitude patterns of customers towards an object. Coffee shops are currently popular with the public, but not many people understand about them. The objectives of this study include determining the characteristics of coffee shop consumer behavior, a literature study of coffee shop consumer behavior, and a proposal for a research title related to coffee shop consumer behavior. The research method was carried out using the customer characteristic question method and a literature study of coffee shop consumer behavior. The results of the study concluded that the characteristics of coffee shop consumer behavior include questions about gender, income or pocket money, occupation, coffee drinking time, visiting hours, visit intensity, type of visit, expenditure, people who visit with customers, reasons for visiting, and social media. Previous studies related to coffee shops include the concept of coffee shops, customer loyalty, customer satisfaction, service, innovation, atmosphere, price, experience, and digital marketing and social media. And proposed research related to coffee shops includes the concept of coffee shops, customer loyalty, customer satisfaction, service, innovation, atmosphere, price, experience, and digital marketing and social media. Further research suggestions should focus on one of the variables related to marketing management and coffee shop consumer behavior.